Youth’s Role in Channeling Community Aspirations for Empowerment in Central Praya District - M. Fathul Hadi; Suranto Aw; Budiman Budiman (Electronic Journal of Education, Social Economics and Technology, 2025)
Youth are often positioned as agents of change with the capacity to contribute significantly to sustainable development. However, their role in community empowerment, particularly in rural areas, remains underexplored. This study aims to examine the strategic role of youth in channeling community aspirations and implementing empowerment initiatives in Central Praya District, West Nusa Tenggara, Indonesia. Using a qualitative descriptive approach, the research involved 35 purposively selected participants, including youth leaders, community figures, and local government representatives. Data were collected through in-depth interviews, observations, and document analysis, and analyzed using Miles and Huberman’s interactive model. The findings reveal that youth play a vital role in three core areas: (1) communicating and collecting public aspirations through both digital and direct channels, (2) facilitating participatory planning and execution of empowerment programs, and (3) addressing internal and external obstacles to community involvement. Despite facing challenges such as low public trust and weak institutional support, youth demonstrated resilience, adaptability, and innovation in promoting inclusive development. The study concludes that effective youth engagement can strengthen participatory governance, improve service delivery, and foster social solidarity at the grassroots level. The implication is that empowerment policies should provide more space, trust, and resources for youth-led initiatives. Strengthening collaboration among youth, communities, and local governments is essential for sustainable and community-based development.